Improving the quality of the intensive care follow-up of ventilated patients during a national registration program. (July 2017) - Reper, P.; Dicker, D.; Damas, P.; Huyghens, L.; Haelterman, M.
Abstract: Objectives: The Belgian Public Health Organization is concerned with rates of hospital-acquired infections like ventilator-associated pneumonia (VAP). Implementing best practice guidelines for these nosocomial infections has variable success in the literature. This retrospective study was undertaken to see whether implementation of the evidence-based practices as a bundle was feasible, would influence compliance, and could reduce the rates of VAP. Study design: We utilized easily collectable data about regular care to rapidly assess whether interventions already in place were effectively successfully applied. This avoided cumbersome data collection and review. Methods: Retrospective compliance rates and VAP ratios were compared using z tests with P -values < 0.05 considered statistically significant. This data review attempted to examine the impact of education campaigns, staff meetings, in-services, physician checklist, nurse checklist, charge nurse checklist implementation, systematic VAP bundle application, and systematic protocols for oral care and sedation protocols. Additionally, VAP ratio could be registered by the participating centers. Results: A total of 10, 211 intensive care unit (ICU) patients were included in the study which represents 66, 817 ICU days under artificial ventilation with an endotracheal tube. The general compliance for VAP bundle raised from VAP was 61% in February 2012 and 74.16% in December 2012 ( P < 0.001). The incidence rate of VAP went from 8.34 occurrences/1000 vent days in 2009 to 4.78 occurrences/1000 vent days in 2012 ( P < 0.001—Pearson test). Conclusions: Efforts to improve physician and staff education, and checklist implementation resulted in an increase in compliance for VAP bundle and a decrease in VAP ratio. This study confirms the applicability of best practice guidelines about regular care but results on VAP incidence have to be confirmed. Highlights: Efforts to improve physician and staff education, and checklist implementation resulted in an increase in compliance for ventilator-associated pneumonia (VAP) bundle, a local reflection on specific practices like oral care and sedation protocols and in a decrease in VAP ratio. This study confirms the applicability of best practice guidelines and suggests a benefit to the use of checklists proposed by the Health Organization. We utilize a practical approach for examining the success of these changes.